Can cognitive capital sustain customer satisfaction? The mediating effects of employee self-efficacy - Mansour Abdullah Alyahya; Elsayed Mohamed; Raphaël Akamavi; Ibrahim A. Elshaer; Alaa M. S. Azzaz (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Despite the important role of cognitive capital as a facet of social capital, there is little empirical work examining the causal effect of cognitive capital dimensions on sustaining customer satisfaction. Thus, there is a need to investigate the relationship between these constructs via employee self-efficacy. Our proposed hypothetical framework is tested in the tourism industry sector employing a quantitative research method. Drawing from social capital and social cognitive theories, we generated items from a piloted questionnaire which was administered to 600 top and middle managers in hotels and travel agents using drop and collect methods. We test our hypothetical model using SEM techniques with 490 usable cases. The survey results indicate that cognitive capital dimensions have direct and indirect relationships with sustained customer satisfaction. In addition, employee self-efficacy mediates between exogenous constructs and the endogenous construct. Surprisingly, these two exogenous constructs: shared norms and shared values do directly influence shared goals and enhance employee self-efficacy. Additionally, shared goals enhance employee efficacy which subsequently leads to sustained customer satisfaction. These findings shed light on the impact of intra-firm social interactions on customer experience in hotels and travel agents. Managers should use cognitive capital to improve the level of service employee self-efficacy and subsequently sustain customer satisfaction. The paper outlines theoretical and managerial implications and addresses possible directions for further research.
Keywords: 650; cognitive capital; employee self-efficacy; shared goals; shared norms; shared values; sustained customer satisfaction